Advancing precision medicines for ocular disorders: Diagnostic genomics to tailored therapies - Panikker, Priyalakshmi; Roy, Shomereeta; Ghosh, Anuprita; Poornachandra, B.; Ghosh, Arkasubhra (Frontiers in Medicine, 2022)
Successful sequencing of the human genome and evolving functional knowledge of gene products has taken genomic medicine to the forefront, soon combining broadly with traditional diagnostics, therapeutics and prognostics in patients. Recent years have witnessed an extraordinary leap in our understanding of ocular diseases and their respective genetic underpinnings. As we are entering the age of genomic medicine, rapid advances in genome sequencing, gene delivery, genome surgery and computational genomics enable an ever-increasing capacity to provide a precise and robust diagnosis of diseases and the development of targeted treatment strategies. Inherited retinal diseases are a major source of blindness around the world where a large number of causative genes have been identified, paving the way for personalized diagnostics in the clinic. Developments in functional genetics and gene transfer techniques has also led to the first FDA approval of gene therapy for LCA, a childhood blindness. Many such retinal diseases are the focus of various clinical trials, making clinical diagnoses of retinal diseases, their underlying genetics and the studies of natural history important. Here, we review methodologies for identifying new genes and variants associated with various ocular disorders and the complexities associated with them. Thereafter we discuss briefly, various retinal diseases and the application of genomic technologies in their diagnosis. We also discuss the strategies, challenges and potential of gene therapy for the treatment of inherited and acquired retinal diseases. Additionally, we discuss the translational aspects of gene therapy, the important vector types and considerations for human trials that may help advance personalized therapeutics in ophthalmology. Retinal disease research has led the application of precision diagnostics and precision therapies, therefore this review provides a general understanding of the current status of precision medicine in ophthalmology.